THE ROLE OF THE PHILOSOPHY OF SCIENCE IN THE DEVELOPMENT OF EDUCATIONAL TECHNOLOGY - Alyan Fatwa (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2025)
Philosophy of science, as a discipline that examines the nature of knowledge, the ways of acquiring knowledge, and its application in human life, plays a strategic role in understanding and formulating the direction of educational technology development. This research aims to explore the role of the philosophy of science in developing educational technology, highlighting how philosophical thinking can guide the design, implementation, and evaluation of more humanistic and meaningful educational technology. This research uses a qualitative approach with descriptive analysis to explore the relevant literature on the relationship between the philosophy of science and educational technology. The research results show that the philosophy of science provides a strong foundation for understanding how educational technology can be used to support more effective, inclusive, and sustainable learning. Moreover, the philosophy of science plays a role in guiding educational technology to remain oriented towards profound educational values, such as freedom of thought, critical thinking, and creativity. The conclusion of this research is that the philosophy of science serves as an important theoretical foundation in the development of educational technology and as a critical reflection tool necessary to create a balance between technological advancement and profound educational goals.